THE USE OF HEARING MEDIA IN INCREASING RESTATION STUDY BIOLOGY STUDENTS CLASS XI IPA SMA NW MATARAM SCHOOL YEAR 2020/2021 - mahnep mahnep; Raden Didi Kuswara (Jurnal Inovasi Pendidikan dan Sains, 2022)
Based on experience and observation, that the biological learning process at SMA NW Mataram, generally still uses a classic approach pattern, teachers dominate the learning process by talking, reading, doing tasks and training to answer questions, while students only sit, listen, record, memorize and do problem exercises. So that the author tried alternatives in using media in the learning process, one of which was with the hearing media, namely learning with VCD aids, televisions and CD cassettes by Harun Yahya entitled "the miracle of human creation". The aim of this study is to improve students' learning achievement with the help of hearing media and improve students' understanding of the basic competencies that exist in biology subjects. In this study, the subject of the study was a student of SMA NW Mataram, class XI IPA semester (even), school year 2020/2021. The students numbered 24 people consisting of men totaling 9 people and women 15 people. Based on the results of the evaluation so far, researchers found that the daily repeat score of each student ≤ 6.5, the average in class XI IPA reached a learning level of 45%. The results showed that based on the results of student learning evaluations, the average test score in cycle I was 6.12 with a classical graduation percentage of 81.82%., Furthermore, the average test in cycle II is 6.50 with a classic graduation percentage of 90.48%, there is an increase in both the average score and the graduation percentage. The next average test score of cycle III is 7.62 with a classic pass percentage of 95.65%, there is also a significant increase. Likewise, the results of observations on teacher activities in learning, in general, showed excellent category results, reaching 80.56% and 88.89% in cycles I and II, then 94.44% in cycle III. From the results of this study, it can be concluded that the application of hearing media to biological learning can improve students' learning achievements and can improve students' understanding of the basic competencies that exist in biology subjects.